Critical appraisal of the mutual engagement of the African states in the african peer review and universal periodic review mechanisms : a human rights perspective - Quashigah, Edward Kofi (University of Pretoria, 2011)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2010.